2018
DOI: 10.1002/acn3.561
|View full text |Cite
|
Sign up to set email alerts
|

Elevated LGI1‐IgG CSF index predicts worse neurological outcome

Abstract: To determine whether CSF leucine‐rich glioma‐inactivated 1(LGI1)‐IgG titer, index or IgG subclass has prognostic significance, we tested serum and CSF specimens collected concomitantly from 39 seropositive patients. LGI1‐IgG index was elevated (>1) in 21 patients (54%), suggesting intrathecal synthesis. Patients with worse outcome at last follow‐up (modified Rankin Scale >2) had significantly higher index (median 6.57 vs. 0.5, P = 0.048) compared to those with better outcome. Higher CSF LGI1‐IgG4 subclass‐spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 18 publications
4
40
1
Order By: Relevance
“…Of interest, it has recently been observed that intrathecal LGI1 antibody synthesis correlates with a poorer prognosis. 16 However, the lack of CSF LGI1 antibodies in some of our patients with striking intrathecal SHM may suggest that DIRS provides a more sensitive measure of B-cell activity.…”
Section: Discussionmentioning
confidence: 72%
“…Of interest, it has recently been observed that intrathecal LGI1 antibody synthesis correlates with a poorer prognosis. 16 However, the lack of CSF LGI1 antibodies in some of our patients with striking intrathecal SHM may suggest that DIRS provides a more sensitive measure of B-cell activity.…”
Section: Discussionmentioning
confidence: 72%
“…Although immunotherapy is fast and efficient in some LGI1 encephalitis patients, other cases are characterized by a long and continuously progressing disease process, including memory deficits, apathy, and difficulties with spatial orientation . Recent studies indicated that a high CSF index and specific IgG isotypes might be predictive of refractory symptoms and cognitive impairment . In a patient with a long‐lasting progressive LGI1 encephalitis (AIE060), our screen detected LGI1 antibodies of IgG1, IgG2, and IgG4 subtype in CSF ASCs and MBCs.…”
Section: Discussionmentioning
confidence: 88%
“…4 Recent studies indicated that a high CSF index and specific IgG isotypes might be predictive of refractory symptoms and cognitive impairment. 9,44 In a patient with a long-lasting progressive LGI1 encephalitis (AIE060), our screen detected LGI1 antibodies of IgG1, IgG2, and IgG4 subtype in CSF ASCs and MBCs. In contrast, in Patient AIE054, we found exclusively antibodies of IgG2 isotype in ASCs.…”
mentioning
confidence: 95%
See 2 more Smart Citations